GENERALIZED OF PERSON IN CONSTRUCTI - Korpalo, O. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines ways of expression of the generalized person; structural-semantic features of generalized personal sentences are described and their groups by gradation degree are allocated.